2017
DOI: 10.3389/fmicb.2017.00602
|View full text |Cite
|
Sign up to set email alerts
|

Genomic and Transcriptomic Insights into Calcium Carbonate Biomineralization by Marine Actinobacterium Brevibacterium linens BS258

Abstract: Calcium carbonate (CaCO3) biomineralization has been investigated due to its wide range of scientific and technological implications, however, the molecular mechanisms of this important geomicrobiological process are largely unknown. Here, a urease-positive marine actinobacterium Brevibacterium linens BS258 was demonstrated to effectively form CaCO3 precipitates. Surprisingly, this bacterium could also dissolve the formed CaCO3 with the increase of the Ca2+ concentration. To disclose the mechanisms of biominer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
24
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(26 citation statements)
references
References 42 publications
2
24
0
Order By: Relevance
“…Our results also suggest that Ca is an important signal messenger in this bacterium since many DEGs were associated with signal binding, transport and transcriptional regulation. Similar results were observed in other transcriptome analysis of bacterial responses to Ca (Oomes et al, 2009;Gode-Potratz et al, 2010;Parker et al, 2016;Zhu et al, 2017).…”
Section: Functional Classification Of Differentially Expressed Genes supporting
confidence: 89%
“…Our results also suggest that Ca is an important signal messenger in this bacterium since many DEGs were associated with signal binding, transport and transcriptional regulation. Similar results were observed in other transcriptome analysis of bacterial responses to Ca (Oomes et al, 2009;Gode-Potratz et al, 2010;Parker et al, 2016;Zhu et al, 2017).…”
Section: Functional Classification Of Differentially Expressed Genes supporting
confidence: 89%
“…The cell surface can act as a nucleation site for mineralization in induced biomineralization (SchultzeLam et al, 1996). Since properties are different for gram positives and gram negatives, both binding divalent cations such as Mg 2+ or Ca 2+ , a determination of the microbial clades is necessary (Chahal et al, 2011;Douglas and Beveridge, 1998;Zhu et al, 2017). Depending on different cell surface structures, different crystal morphologies have been reported (Cao et al, 2016;Seifan et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…For the constant salinity condition, the identified phylotypes with >1% relative abundance reported for calcite precipitation were Nocardioides (1.163% to 1.694%) [31], Brevibacterium (0.604% to 2.324%) [32], and Pseudomonas (0.671% to 2.284%) [33]. For the case of struvite precipitation, the identified phylotypes were Corynebacterium (0.492% to 2.374%) [34], Brevibacterium (0.604% to 2.324%) [35], and Ochrobactrum (0.671% to 2.284%) [15].…”
Section: Identification Of Bacterial Species Associated With Mineral mentioning
confidence: 99%
“…Genomic insights into the formation of calcite by Brevibacterium linens have shown that this species regulates three carbonic anhydrases in response to Ca 2+ concentration in the precipitation medium [32]. The relative abundance of Brevibacterium in the biofouling of the variable salinity scenario ranged from 0.007% to 0.009%.…”
Section: Identification Of Bacterial Species Associated With Mineral mentioning
confidence: 99%